What Caused the Big Bang? - Edwards, Rem B. (Philosophy and Religion, 2021)
This book critically explores answers to the big question, What produced our universe around fifteen billion years ago in a Big Bang? It critiques contemporary atheistic cosmologies, including Steady State, Oscillationism, Big Fizz, Big Divide, and Big Accident, that affirm the eternity and self-sufficiency of the universe without God. This study defends and revises Process Theology and arguments for God's existence from the universe's life-supporting order and contingent existence.